Dynamic and Widespread lncRNA Expression in a Sponge and the Origin of Animal Complexity - Gaiti, Federico (Mol Biol Evol, 2015)
Long noncoding RNAs (lncRNAs) are important developmental regulators in bilaterian animals. A correlation has been claimed between the lncRNA repertoire expansion and morphological complexity in vertebrate evolution. However, this claim has not been tested by examining morphologically simple animals. Here, we undertake a systematic investigation of lncRNAs in the demosponge Amphimedon queenslandica, a morphologically simple, early-branching metazoan. We combine RNA-Seq data across multiple developmental stages of Amphimedon with a filtering pipeline to conservatively predict 2,935 lncRNAs. These include intronic overlapping lncRNAs, exonic antisense overlapping lncRNAs, long intergenic nonprotein coding RNAs, and precursors for small RNAs. Sponge lncRNAs are remarkably similar to their bilaterian counterparts in being relatively short with few exons and having low primary sequence conservation relative to protein-coding genes. As in bilaterians, a majority of sponge lncRNAs exhibit typical hallmarks of regulatory molecules, including high temporal specificity and dynamic developmental expression. Specific lncRNA expression profiles correlate tightly with conserved protein-coding genes likely involved in a range of developmental and physiological processes, such as the Wnt signaling pathway. Although the majority of Amphimedon lncRNAs appears to be taxonomically restricted with no identifiable orthologs, we find a few cases of conservation between demosponges in lncRNAs that are antisense to coding sequences. Based on the high similarity in the structure, organization, and dynamic expression of sponge lncRNAs to their bilaterian counterparts, we propose that these noncoding RNAs are an ancient feature of the metazoan genome. These results are consistent with lncRNAs regulating the development of animals, regardless of their level of morphological complexity.